Political legitimacy and research ethics. (23rd August 2018) - Smith, Maxwell J.; Weinstock, Daniel
Abstract: In democratic theory, "legitimacy" refers to the set of conditions that must be in place in order for the claims to authority of somebody to be deemed appropriate, and for their claims to compliance to be warranted. Though criteria of legitimacy have been elaborated in the context of democratic states, there is no reason for them not to be drawn up, with appropriate amendments, for other kinds of authority structures. This paper examines the claims to authority made over researchers by international bodies governing research ethics, who exercise their authority by the research ethics guidelines they produce (including recent revisions to the Declaration of Helsinki and CIOMS Guidelines). We argue that discussions of such bodies and sets of guidelines often elide questions of justification and questions of legitimacy, and that the grounds that might allow us to mount a strong case for the latter are at present sorely underdeveloped.